2012
DOI: 10.3390/molecules171214778
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel ~18 kDa Antioxidant Protein from Ginkgo biloba Seeds

Abstract: Ginkgo biloba seeds are widely used as a food and traditional medicine in China. In the present study, a novel antioxidant protein named GBSP was purified from Ginkgo biloba seeds. The protein (GBSP) was purified by homogenization of Ginkgo biloba seed powder in saline solution, 70% ammonium sulphate precipitation, filtration on a DEAE-Cellulose52 anion exchange column, gel filtration on a Sephadex G-50 column, and preparative chromatography on a C18 column using RP-HPLC. GBSP showed an apparent molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…6,11,12 However, bioactive peptides isolated from vegetable protein hydrolysates are becoming important, since they are a more economical and accessible alternative to proteins from animal sources. 13 Several studies have described the production of chelating peptides, which also exert antioxidant activity in the presence of transition metals, from proteins of plants such as Phaseolus vulgaris (bean), 14 Jatropha curcas (physic nut), 15 Helianthus annuus (sunflower), 16 Zea mays (corn), 17 Ginkgo biloba (maidenhair tree) 18 and Ipomoea batatas (sweet potato). 19 Also, in previous studies we showed that hydrolysis of Cicer arietinum L. (chickpea) proteins with the digestive enzymes pepsin and pancreatin produced copper-and iron-chelating peptides, which were purified by affinity chromatography through immobilized copper.…”
Section: Introductionmentioning
confidence: 99%
“…6,11,12 However, bioactive peptides isolated from vegetable protein hydrolysates are becoming important, since they are a more economical and accessible alternative to proteins from animal sources. 13 Several studies have described the production of chelating peptides, which also exert antioxidant activity in the presence of transition metals, from proteins of plants such as Phaseolus vulgaris (bean), 14 Jatropha curcas (physic nut), 15 Helianthus annuus (sunflower), 16 Zea mays (corn), 17 Ginkgo biloba (maidenhair tree) 18 and Ipomoea batatas (sweet potato). 19 Also, in previous studies we showed that hydrolysis of Cicer arietinum L. (chickpea) proteins with the digestive enzymes pepsin and pancreatin produced copper-and iron-chelating peptides, which were purified by affinity chromatography through immobilized copper.…”
Section: Introductionmentioning
confidence: 99%
“…The protein content of Ginkgo biloba seed is around 10% (dry mass). Ginkgo biloba seed protein is considered to be a high-quality protein and exhibits strong antioxidant properties (Huang et al, 2010;Zhou et al, 2012). The protein polypeptide chain contains various functional areas that are considered bioactive with respect to antioxidant property.…”
mentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) has become an important tool of choice for large molecular analyses, especially for proteins. The proteome profiling technique by MALDI-TOF-MS provided a broad-base and effective approach for the identification of proteins with biological activity [ 24 , 25 ]. In the present investigation the gel band of F3 was excised from Coomassie Blue-stained gel and further processed for MALDI-TOF-MS analysis.…”
Section: Resultsmentioning
confidence: 99%